Phonetics Learning Anxiety – Results of a Preliminary Study - Baran-Łucarz, Małgorzata (Research in Language, 2013)
The main aim of this paper is to verify the assumption that pronunciation learning during a course of phonetics is hindered by the feeling of anxiety (Phonetics Learning Anxiety) experienced by foreign language (FL) learners studying English as their major at universities or colleges. A study carried out among 32 students of the School of English at Wroclaw University (Poland) revealed a significant negative correlation of moderate strength between the subjects’ level of Phonetics Learning Anxiety (PhLA) and their attainments on pronunciation tests (sentence, passage and word reading) conducted after a 45-hour (30x90-minute lessons) course of practical phonetics. The detrimental effect of PhLA on pronunciation learning was further supported by t-tests, in which the pronunciation of high anxiety subjects was found to be at a significantly lower level than that of low anxiety students. The Phonetics Learning Anxiety Scale, a 44-item questionnaire based on a 6-point Likert scale, designed for the purpose of the research sheds light on the nature of this peculiar type of apprehension experienced by advanced FL learners in a specific educational context (i.e. a traditional classroom, rather than a language or computer laboratory), in which the major focus is on pronunciation practice. The obtained quantitative data imply that such factors as fear of negative evaluation (represented by general oral performance apprehension and concern over pronunciation mistakes, pronunciation self-image, pronunciation self-efficacy and self-assessment) and beliefs about the nature of FL pronunciation learning are significant sources of PhLA. Anxiety about the transcription test (IPA Test Anxiety) - one of the other hypothetical determinants of PhLA - did not prove to be correlated with the general level of Phonetics Learning Anxiety.